EFEKTIFITAS KONSELING BEHAVIORAL DENGAN TEKNIK DESENSITISASI SISTEMATIS UNTUK MEREDUKSI KECEMASAN MENGHADAPI UJIAN SEMESTER MAHASISWA - Ahmad Yusuf (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2021)
This study examines the application of relaxation as a technique of counseling guidance to reduce anxiety in facing semester exams at STKIP Andi Matappa. The objectives of this study were: (1) to find out how the description of the implementation of systematic desensitization behavioral counseling techniques in reducing anxiety in facing student semester exams at STKIP Andi Matappa, (2) knowing how to describe the level of anxiety facing student semester exams before and after giving behavioral counseling of desensitization techniques systematic at STKIP Andi Matappa, and (3) knowing whether there is an effect of the application of systematic desensitization technique behavioral counseling on anxiety facing student semester exams at STKIP Andi Matappa. The results showed: (1) The level of student anxiety in facing the semester exams at STKIP Andi Matappa during the implementation of systematic desensitization technique behavioral counseling was in the very high category. (2) The level of student anxiety in facing semester exams at STKIP Andi Matappa during the implementation of systematic desensitization technique behavioral counseling is in the high category. (3) there is an influence on the level of student anxiety in facing the semester exams at STKIP Andi Matappa at the time of implementing the systematic desensitization technique behavioral counseling is in the low category.